Bioprospecting of Pectinase-Producing Bacteria from Marine Actinomycetes - Neneng Hasanah; Hana Nadhifah; Mulyorini Rahayuningsih; Akhirta Atikana; Shanti Ratnakomala; Puspita Lisdiyanti; Nanik Rahmani (Jurnal Ilmu Pertanian Indonesia, 2025)
Pectinase is used in a variety of industries, including fruit juice production, textile processing, papermaking, biodegumming, coffee and tea manufacturing, medicines, feed, and nutraceuticals. The demand for pectinase enzymes grows year after year. Industrial applications require high-activity enzymes that can increase considerable product yields while also improving based on needs and byproduct use. Indonesia's industry continues to rely on imported pectinase enzymes. Indonesia, on the other hand, possesses megabiodiversity, particularly marine microorganisms, which have the potential to provide new enzymes with high activity for industrial applications. This work aims to undertake bioprospecting of marine actinomycetes producing pectinase enzymes that have the capacity to hydrolyze pectin polymer, both from commercial and biomass sources. A total of 20 marine actinomycetes isolates from sediment, seawater, and sponges were bioprospected, and one isolate was selected with high pectinase activity (BLH 1.20), which was then used to characterize pH, temperature, hydrolysis analysis on pectin polymers, and isolate identification using 16s rRNA analysis. The selected isolate (BLH 1.20) performed best in a sodium phosphate buffer with a pH of 6.0 and a temperature of 30°C, achieving an activity of 5.4 U/mL. The 16S rRNA analysis revealed that the isolate is from the genus Streptomyces and the species Streptomyces sampsonii. Keywords: bioprospecting, marine Actinomycetes, pectinase, Streptomyces sampsonii